Gingival changes in a drug-induced gingival overgrowth patient using tacrolimus: a case report - KURU, LEYLA (AVES PRESS LTD, 2015)
This case report presents a 33 year-old female renal transplant recipient who presented to our clinic with her chief complaint of gingival overgrowth. Following clinical and radiographic examinations, she was diagnosed with chronic periodontitis accompanied by cyclosporin A and nifedipine-induced gingival overgrowth. Initial periodontal therapy and replacement of cyclosporin A with tacrolimus, with continued nifedipine usage, were performed. Marked improvements in clinical parameters were observed within 3 months. Bilateral ulcerated lesions which were observed on attached gingiva of the upper and lower premolar regions 2 months after commencement of tacrolimus usage, were histopathologically examined and diagnosed with nonspecific ulcerations. These lesions disappeared within 2 months after the dose of tacrolimus was decreased. In this case report, a renal transplant patient with chronic periodontitis and gingival overgrowth was treated with scaling/root planning and conversion from cyclosporin A to tacrolimus. Ulcerations on the gingiva were assumed to have resulted from tacrolimus usage.
Keywords: Gingival overgrowth; cyclosporin A; tacrolimus